Performance assessment of domestic photovoltaic power plant with a storage system. Issue 11 (2018) - Chiacchio, Ferdinando; D'Urso, Diego; Aizpurua, Jose Ignazio; Compagno, Lucio
Abstract: Grid-connected low voltage photovoltaic power plants cover the majority of the power capacity installed in Italy. They offer an important contribution to the power demand of the utilities connected but, due to the nature of the solar resource, the night time consumption can be satisfied only withdrawing the energy by the national grid, at the price of the energy distributor. Thanks to the improvement of storage technologies and the decreasing of costs, the installation of a system of battery looks a promising solution. In this paper, a model-based approach to analyze and discuss the performance of a domestic photovoltaic power plant with a storage system is presented.